2012
DOI: 10.1136/bcr-03-2012-6050
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic haematological malignancy presenting as a sellar mass

Abstract: SummaryA man in his 60s with a history of multiple myeloma diagnosed 6 months previously was referred with a diagnosis of a sellar mass. He reported a 3-month history of headaches associated with double vision which appeared to improve with corticosteroid treatment. An MRI scan revealed a 3.7 cm×3 cm×2.6 cm sellar mass with erosion into the sphenoid sinus and extending to the right cavernous sinus. Pituitary function tests were normal apart from hypogonadotrophic hypogonadism. A diagnosis of plasmacytoma was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Data regarding the anterior pituitary function in patients with sellar plasmacytomas are not always reported, but it is usually well preserved ( 3 , 5 , 6 , 7 , 8 , 9 ), unlike our case. Lee and coworkers ( 6 ) present 1 patient with hypogonadotrophic hypogonadism and 1 patient with hyperprolactinemia, without hypopituitarism.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Data regarding the anterior pituitary function in patients with sellar plasmacytomas are not always reported, but it is usually well preserved ( 3 , 5 , 6 , 7 , 8 , 9 ), unlike our case. Lee and coworkers ( 6 ) present 1 patient with hypogonadotrophic hypogonadism and 1 patient with hyperprolactinemia, without hypopituitarism.…”
Section: Discussioncontrasting
confidence: 57%
“…In their review, they mention 38% (of 26 patients with reported prolactin levels) with hyperprolactinemia and 15% (of 33 patients with reported endocrine evaluation) with hypopituitarism (including their own). The hypopituitarism cases included a patient reported by Sinnot and coworkers ( 5 ) with inappropriately normal LH and FSH for a menopausal woman (and minimally elevated prolactin levels); a patient described by Joukhadar and coworkers ( 7 ) with central hypothyroidism (and hyperprolactinemia); a patient described by Udiawar and coworkers ( 3 ) who complained of loss of libido and reduced frequency of erection that turned out to have low testosterone levels, with normal FSH and LH levels (although the authors interpreted this result as possible hypogonadotrophic hypogonadism, they did not perform a LHRH stimulation test to confirm it, at least it is not described in their paper). Less robust cases reviewed included a patient with slightly impaired cortisol response to insulin-induced hypoglycemia and a borderline low response of TSH to TRH stimulation test and a case of isolated low testosterone levels with no mention to FSH and LH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report a rare case of a solitary sellar plasmacytoma, which initially masqueraded as temporal arteritis. So far, 36 cases of sellar plasmacytomas have been reported in the literature ( 2 , 3 , 5 , 6 , 7 ), but only eight cases were classified as solitary plasmacytomas ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Solitary plasmacytomas are uncommon and can either arise from bone or soft tissue ( 1 ). Solitary sellar plasmacytomas are exceedingly rare and to date there has only been eight reported cases without progression to multiple myeloma ( 2 , 3 , 4 , 5 , 6 , 7 ). Clinically and radiologically, sellar plasmacytomas mimic benign pituitary tumors, which make the differential diagnosis difficult ( 3 , 6 ).…”
Section: Introductionmentioning
confidence: 99%